FACTORS THAT AFFECT THE INCIDENCE OF STUNTING IN TOODDLERS AGED 6-59 MONTHS - Lili Rahmawati; Susy Sriwahyuni; Enda Silvia Putri (RADJA PUBLIKA, 2022)
Based on WHO data (2018), the average prevalence of stunting under five in Indonesia in the 2005-2017 range is 36.4%. Indonesian Toddler Nutritional Status Survey (SSGBI) in 2019 shows the prevalence of stunting under five in Aceh province is 33.6%. Meanwhile, for West Aceh district, the prevalence of stunting under five is quite high, at 40.4%. The high prevalence of stunting in West Aceh is still an important health problem to overcome because children are the nation's assets in the future. Objective: to determine the factors that influence the incidence of stunting in Kaway XVI sub-district. Methods: Quantitative research with Cross Sectional Study approach. The population in this study were all toddlers aged 0-59 months totaling 126 toddlers and the research sample was toddlers aged 6-59 months, with the sampling method using purposive sampling technique with a total of 117 samples. Results: The results showed that there was no significant effect between exclusive breastfeeding (p: 0.683), feeding patterns (p: 0.376), and mother's knowledge (p: 0.483) on the incidence of stunting, and there was a significant effect between maternal education (p: 0.018) on the incidence of stunting in toddlers aged 6-59 months in Kaway XVI sub-district.